Gratification sought and obtained in smartphone usage among undergraduates in Selangor, Malaysia - Mohd Mothar, Noor Mayudia (2013)
The smartphone is used to search for information, sought entertainment, integrated in social interaction, as well as represents personal identity. This study applies the Uses and Gratification Theory to explain the gratification sought and obtained from the use of smartphones from the McQuail’s (1983) typologies such as information, personal identity, integration and social interaction, and entertainment. This study determined the rank of importance between the four typologies for these youth, and also the influenced of the smartphone has in youth’s perception towards these typologies. Furthermore, this study also identified the roles of the smartphone in shaping the way youth behave towards these typologies, and to determine the consequences the smartphone usages have on them. The research involved undergraduates of public as well as private universities between the ages 18-27 years old. 385 respondents were involved in this research and purposive sampling was used in the sample selection. The study was conducted on youths specifically undergraduate students who owned smartphones and living in the urban area. This is a quantitative research that conclusive of structured survey questionnaire that was distributed to the samples that aimed to seek the information that describe youths’demographic, and which typologies are ranked the most important. The statistical procedures used include descriptive, and inferential statistics. The results revealed that Personal Identity was the most important typology and it was also identified as the reason why the respondents used their smartphone. The relationship between Gratification Sought and Gratification Obtained for Personal Identity is strongly positive. McQuail’s typology of Gratification Sought and Gratification Obtained from the media was proved to be important for this research as it helps to clarify the question regarding the smartphone’s usage and its significance to the respondents.